Older people's perceived causes of and strategies for dealing with social isolation - Pettigrew, Simone; Donovan, Robert; Boldy, D.; Newton, R. (Routledge, 2014)
Objective: To explicate lay theories relating to social isolation and to identify instances of positive deviance to inform future efforts to encourage older people to participate in protective behaviors. Method: Twelve focus groups and 20 individual interviews were conducted with Australians aged 40 years and older. Data were collected in metropolitan and regional areas. The age threshold was based on the need to generate formative research to inform interventions to encourage people to engage in preventive behaviors prior to reaching older age when they become more susceptible to social isolation. Results: Two primary lay theories were identified in the data. These are related to the recognized importance of social connection and the belief that forming new social connections becomes more difficult with age due to a range of individual and external factors. Examples of positive deviance that were identified included viewing overcoming social isolation as an incremental process, being prepared to be the instigator of social interaction, and adopting an external focus. Conclusion: The findings suggest that the provision of a broad range of group activities may need to be combined with a focused approach to targeting and approaching those most at risk to reduce the burden of social isolation at a population level.